Taxonomic implications from morphological and anatomical studies in the section Stenodiptera from the genus Grammosciadium (Apiaceae) - Bani, Baris; Ulusoy, Fatma; Karakaya, Muhammet Ali; Koch, Marcus A. (Pensoft Publishers, 2016)
Grammosciadium pterocarpum subsp. bilgilii and Grammosciadium pterocarpum subsp. sivasicum from Turkey are herein described as two new subspecies, and the species Grammosciadium schischkinii is synonymied under Grammosciadium pterocarpum subsp. pterocarpum. Quantitative variation of morphological and anatomical characters have been analysed to provide discriminative characters between the taxa of section Stenodiptera and to provide a key to the species. The taxonomic status of the taxa has been discussed in light of these morphological and fruit anatomical data using multivariate statistics such as MANOVA and Principal Component Analysis. The results are also used to present a critical discussion of characters used to distinguish and determine different taxa within Grammosciadium. MANOVA showed that ten characters, except stylopodium and style length, differed significantly among the taxa, and the results were confirmed by Tukey tests and PCA analysis (except the character of fruit number). However, only ranges of the characters of sepal length, fruit length, fruit width, fruit width/wing width ratio, and width of fruit wing are not overlapped. Qualitative characters of petiolate stipular segments of lower leaves and presence of funicular oil ducts in transvers section of mericarps were found as diagnostic characters.
Keywords: PCA; taxonomy; Stenodiptera; Turkey; Grammosciadium; MANOVA; Research Article; 15. Life on land